Einfluss des arktischen Meereises auf das Klima der Nordhemisphäre - Harlaß, Jan (2011)
This thesis investigates the influence of arctic sea ice on the winter climate in the 20th century in a high resolution general circulation model (ECHAM5.3, T213). For all seasons in the perturbed simulation sea ice cover (SIC) is replaced by open water at the freezing point, which is then compared with the control run. The effect of completely reduced SIC is then assessed and compared to the effect of an anthropogenic global temperature rise in the projected future summer climate at the end of 21th century (A1B-Szenario scenario), when SIC is reduced to 12% to 20% (August to October)of the SIC in the 20th century. It is shown, that the melting of all sea ice has impacts on the climate in the winter season (January to March) reaching as far south as the subtropics and leads to responses in the dynamic of the atmosphere. The atmospheric warming, caused by an increase of sensible and latent upward heat fluxes from the Arctic Ocean, is conned to the lower troposphere and the high latitudes, whereas temperatures decrease significantly over Siberia. Other than an expected decrease in sea level pressure (SLP), due to the large-scale warming, SLP reduces only in the western Arctic, northeast North America and the North Atlantic, while it increases over northern Asia and Europe as well as over Greenland, which means an intensication and expansion of the Siberian High into the North Atlantic. Due to a smaller meridional temperature gradient, the large-scale atmospheric circulation weakens and moves a little southward, so that the subtropical jet is focused over 30°N. The 10m wind speed decreases in large areas outside the Arctic. Furthermore, the variability of SLP and 2m temperature decrease in the polar region. The leading modes of SLP variability (EOF analysis) are shifted to lower amounts of explained variance, whereby the Arctic Oscillation pattern remains as the dominant mode. Contrary to the 20th century, the planetary circulation in the summer climate of the 21th century strengthens and moves to the North. Zonal ...